1973
DOI: 10.1002/cjce.5450510402
|View full text |Cite
|
Sign up to set email alerts
|

Solids entrainment in a large gas fluidized bed

Abstract: Entrainment from a gas fluidized bed of cracking catalyst in a 2‐ft diameter column equipped with continuous solids recycle has been studied. Radial profiles of entrainment rate and mean particle size were relatively flat. The entrainment rate decreased rapidly with increasing height above the bed and with decreasing fluidizing velocity. The existence of a transport disengaging height above which the entrainment rate and mean particle size become essentially constant was confirmed experimentally. This may be t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

1979
1979
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(23 citation statements)
references
References 8 publications
0
22
0
Order By: Relevance
“…Lewis et al (1962) performed entrainment experiments using column diameter ranging from 0.019 to 0.146 m and concluded that for column diameters greater than 0.08 to 0 1 m, the entrainment or elutriation becomes constant and independent of vessel diameter; however, a sharp rise in entrainment rates was found at small bed diameters (0.009 to 0.02 m). Recently, more data from large-scale fluidized bed have been reported (Fournol et al, 1973;Nazemi et al, 1974;Merrick and Highley, 1974, Large et al, 1976;Colakyan et al, 1979;Lin et al, 1980) It is found that under similar operating conditions, the elutriation rate constant from the large-scale bed tends to be much higher than that from the small-scale bed as shown in Figure 9. At a low gas velocity (particle Reynolds Number less than the critical Reynolds Number), the friction between the particles and the column wall is important.…”
mentioning
confidence: 80%
“…Lewis et al (1962) performed entrainment experiments using column diameter ranging from 0.019 to 0.146 m and concluded that for column diameters greater than 0.08 to 0 1 m, the entrainment or elutriation becomes constant and independent of vessel diameter; however, a sharp rise in entrainment rates was found at small bed diameters (0.009 to 0.02 m). Recently, more data from large-scale fluidized bed have been reported (Fournol et al, 1973;Nazemi et al, 1974;Merrick and Highley, 1974, Large et al, 1976;Colakyan et al, 1979;Lin et al, 1980) It is found that under similar operating conditions, the elutriation rate constant from the large-scale bed tends to be much higher than that from the small-scale bed as shown in Figure 9. At a low gas velocity (particle Reynolds Number less than the critical Reynolds Number), the friction between the particles and the column wall is important.…”
mentioning
confidence: 80%
“…1, the entrainment rate in the freeboard can be represented by the following equation, which is similar to those proposed by few other researchers (Fournol et al, 1973):…”
Section: Backgrounds On Theory and Calculationmentioning
confidence: 84%
“…Amitin et al [32] 0.85U 0.5 (7.33 − 1.2log 10 U) Fournol et al [33] 1000U 2 /g Smolders and Baeyens [34] 6…”
Section: Reference Tdh Correlationmentioning
confidence: 99%